2014
DOI: 10.3389/fgene.2014.00288
|View full text |Cite
|
Sign up to set email alerts
|

Comet assay to measure DNA repair: approach and applications

Abstract: Cellular repair enzymes remove virtually all DNA damage before it is fixed; repair therefore plays a crucial role in preventing cancer. Repair studied at the level of transcription correlates poorly with enzyme activity, and so assays of phenotype are needed. In a biochemical approach, substrate nucleoids containing specific DNA lesions are incubated with cell extract; repair enzymes in the extract induce breaks at damage sites; and the breaks are measured with the comet assay. The nature of the substrate lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 60 publications
3
103
0
6
Order By: Relevance
“…Taking into account that the majority of primary DNA lesions detectable using the alkaline comet assay are potentially repairable, our results mostly indicate the acute effects caused by the tested compounds, and also suggest the differences in their ability to destabilise the integrity of DNA in kidney cells of mice. It is noteworthy to mention here that the alkaline comet assay we used allows a sensitive detection of different forms of primary DNA damage in single cells but the most important among them are DNA strand breaks and alkali-labile sites (8,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that the majority of primary DNA lesions detectable using the alkaline comet assay are potentially repairable, our results mostly indicate the acute effects caused by the tested compounds, and also suggest the differences in their ability to destabilise the integrity of DNA in kidney cells of mice. It is noteworthy to mention here that the alkaline comet assay we used allows a sensitive detection of different forms of primary DNA damage in single cells but the most important among them are DNA strand breaks and alkali-labile sites (8,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the levels of primary DNA damage in hydroquinone-treated lymphocytes, we used an alkaline version of the comet assay, which detects the widest range of lesions (56)(57)(58). First literature reports regarding hydroquinone effects detected by the comet assay in peripheral blood lymphocytes treated in vitro originated from Andreoli et al (59) who found that hydroquinone, along with two other benzene metabolites -benzoquinone and benzenetriol -exerted a significant genotoxic effect on resting lymphocytes, with the lowest effective concentrations below 1 µg mL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of comet assay, the positive results could be attributed to the fact that the transient promutagenic DNA changes, e.g. SSBs, might be quickly repaired (Azqueta et al 2014). Hence, these photogenotoxic findings only have an informative value, in contrast to gene and chromosome mutations.…”
Section: Discussionmentioning
confidence: 89%